Restarting Mass Drug Administration for Neglected Tropical Disease Programs during the COVID-19 Pandemic - Itaye, Tikhala (My University, 2021)
The COVID-19 pandemic has disrupted health services, including neglected tropical disease (NTD) programs. Most mass drug administration (MDA) program activities were postponed for 6-12 months due to the World Health Organization Guidance on COVID-19. NTD-endemic countries seek to rapidly resume activities in order to minimize setbacks to disease control and elimination. To understand the context of restarting MDA programs, an online survey and virtual focus group discussions were conducted with Ministry of Health NTD Program Managers and representatives from Non-Governmental Organizations working in sub-Saharan Africa. MDA programs have suffered major disruptions, particularly due to resource shortages, lack of personal protective equipment for COVID-19 safety precautions and community hesitancy to engage in MDA activities due to fears about coronavirus infection. Solutions for restarting MDA programs were identified, such as focusing on door-to-door treatment instead of fixed point distribution, and using spoons and premeasured envelopes to minimize health worker contact with drugs. Participants suggested that restarting MDA programs might also push NTD programs to innovate in ways that could accelerate NTD progress through integration with other health programs, incorporating mobile technology to collect implementation data and conducting meetings and trainings online.
Thesis (Master's)--University of Washington, 2021
Keywords: Public health; Global Health